Exploring the Relationship between Maternal Anxiety, Sleep Disturbances, and Family Quality of Life in Children with Cerebral Palsy - Serdengeçti, Nihal; Kılıç, Zeynep; Tarçın, Gürkan; Albayrak, Zeynep Seda (Cerrahpaşa Medical Journal, 2024)
Objective: Cerebral palsy (CP) is a chronic condition that can have a significant impact on the quality of life (QoL) of patients and their families. A child’s sleep disturbances and maternal anxiety are common issues in CP; however, their impact on family QoL is not fully understood. This study aimed to investigate the relationship among child’s sleep disturbances, maternal anxiety levels, and family QoL in children CP. Methods: This study included 58 children with CP and 63 typically developing (TD) peers matched for age and sex, along with their mothers. We used the Sleep Disturbance Scale for Children, Beck Anxiety Inventory, and Beach Center Family Quality of Life Scale to assess children’s sleep problems, maternal anxiety, and family QoL, respectively. Regression analysis was conducted to identify other factors that could affect the family QoL. Results: Children with CP had more sleep disturbances, lower family QoL, and higher levels of maternal anxiety compared to their TD peers. Moreover, maternal anxiety was significantly related to family QoL and child’s sleep disturbances in children with CP. Regression analysis revealed that other factors such as age, sex, motor function, having a diagnosis of epilepsy, and cognitive level did not affect family QoL in children with CP. Conclusion: Addressing children’s sleep disturbances and mother’s anxiety can be important for the family QoL of children with CP. Interventions focused on these issues can help this population, but further research is needed to develop effective strategies for enhancing the well-being of children with CP. Cite this article as: Serdengeçti N, Kılıç Z, Tarçın G, Albayrak ZS. Exploring the relationship between maternal anxiety, sleep disturbances, and family quality of life in children with cerebral palsy. Cerrahpaşa Med J. 2024;48(2):129-134.